Biofilm architecture determines the dissemination of conjugative plasmids - Sarah Djermoun; Daniel K. H. Rode; Eva Jiménez-Siebert; Niklas Netter; Christian Lesterlin; Knut Drescher; Sarah Bigot (Proceedings of the National Academy of Sciences, 2025)
Plasmid conjugation is a contact-dependent horizontal gene transfer mechanism that significantly contributes to the dissemination of antibiotic resistance among bacteria. While the molecular mechanisms of conjugation have been extensively studied, our understanding of plasmid transfer dynamics within spatially structured bacterial communities and the influence of community architecture on plasmid dissemination remains limited. In this study, we use live-cell fluorescence microscopy to investigate the propagation of the broad host range RP4 conjugative plasmid in Escherichia coli populations exhibiting varying levels of spatial organization. In high-density, two-dimensional cell monolayers, direct and tight contact between donors and recipients is not only necessary but also sufficient to trigger RP4 plasmid transfer, ensuring optimal plasmid propagation. In three-dimensional mature biofilms, the emergent community architecture limits the ability of donor cells to enter regions with high cell density, which hinders the establishment of direct contacts with recipients and impedes plasmid transfer in biofilms. In contrast, microcolonies, early-stage biofilms, and biofilms with a lower surface coverage leave open access points for donor cells in regions that later emerge as high-cell-density regions in mature biofilms, which facilitates plasmid transfer. These findings reveal the crucial role of bacterial community architecture in determining the efficiency of plasmid dissemination.